An overview to pharmaceutical financing in Iran - Mehdi Varmaghani; Amir Hashemi-Meshkini; Akbar Abdollahiasl; Elham Heidari; Hedieh-Sadat Zekri; Saeed Yaghoubifard; Farid Dorkoosh (Tehran University of Medical Sciences, 2017)
Pharmaceutical expenditure is a substantial part of the health-care system budget. In Iran, people are paying about half of total pharmaceutical expenditure out of their pocket. In this study, we reviewed the Iranian pharmaceuticals financing system including the current situation and the relevant policies. We also provide an overview about the new health-care system reform and its challenges ahead.